Histologic and Histomorphometric Assessment of Sinus Floor Augmentation with Synthetic Hydroxyapatite (Nanobone® ) Alone or in Combination with Plateletrich Fibrin: Clinical Trial - Francisco, Luís Filipe Santos (2024)
Background: Several techniques have been described for maxillary sinus graft augmentation, including the lateral window technique and crestal approach with osteotomes or osseodensification. Platelet-rich fibrin has been used in maxillary sinus lift procedures due to its ability to accelerate soft and hard tissue healing. Objective: The aim of this study was to evaluate the potential of PRF in combination with the synthetic hydroxyapatite Nanobone® to enhance bone regeneration in sinus floor elevation with the lateral window technique. Materials and Methods: Out of 50 individuals screened in a preoperative assessment visit from the CESPU - Famalicão clinical unit and intervened upon between January 2023 and December 2023, only six patients who met the study's inclusion criteria consented to participate. In a split-mouth study, twelve sinus graft surgeries were carried out. Results: Observations reveal that, for the test group (Nanobone®/PRF), there is 27.5 ±4.9% new vital bone, 23.0 ±3.7% inert bone particles, and 49.4 ± 2.8% connective tissue. Meanwhile, for the control group (Nanobone®), there is 19.5 ± 3.0% new vital bone, 23.4 ± 5.7% inert bone particles, and 57.0 ± 3.5% connective tissue. Conclusion: The results strongly indicate that mixing liquid PRF with Nanobone® does not have a negative influence on the amount of viable bone formation, and it seems to slightly increase the amount of new bone formation and revascularization in sinus bone graft procedures with the lateral window technique compared to the single use of Nanobone®.